Assessing absolute changes in breast cancer risk due to modifiable risk factors - Quante, Anne Siobhain; Herz, Julia; Whittemore, Alice S.; Fischer, Christine; Strauch, Konstantin; Terry, Mary Beth (Breast cancer research and treatment, 2015)
Clinical risk assessment involves absolute risk measures, but information on modifying risk and preventing cancer is often communicated in relative terms. To illustrate the potential impact of risk factor modification in model-based risk assessment, we evaluated the performance of the IBIS Breast Cancer Risk Evaluation Tool, with and without current body mass index (BMI), for predicting future breast cancer occurrence in a prospective cohort of 665 postmenopausal women. Overall, IBIS’s accuracy (overall agreement between observed and assigned risks) and discrimination (AUC concordance between assigned risks and outcomes) were similar with and without the BMI information. However, in women with BMI > 25 kg/m2, adding BMI information improved discrimination (AUC = 63.9 % and 61.4 % with and without BMI, P < 0.001). The model-assigned 10-year risk difference for a woman with high (27 kg/m2) versus low (21 kg/m2) BMI was only 0.3 % for a woman with neither affected first-degree relatives nor BRCA1 mutation, compared to 4.5 % for a mutation carrier with three such relatives. This contrast illustrates the value of using information on modifiable risk factors in risk assessment and in sharing information with patients of their absolute risks with and without modifiable risk factors.
Gesehen am 16.07.2020